2014
DOI: 10.3346/jkms.2014.29.2.272
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Incidence of Trichophyton mentagrophytes in Korea: Analysis of 6,250 Cases during the Last 21-Year-Period (1992-2012)

Abstract: Trichophyton mentagrophytes is the second common dermatophyte in Korea. However, few reports have been issued on the epidemiological and mycological characteristics of T. mentagrophytes in Korea based on long-term, large-scale study. The purpose of this study was to elucidate the epidemiological and mycological characteristics of T. mentagrophytes in Korea. During the 21-yr-period from 1992 to 2012, 6,250 patients with T. mentagrophytes were surveyed to determine annual incidence and the distribution of subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 7 publications
0
10
0
3
Order By: Relevance
“…Recently, Lee et al ( 19 ) also reported that the prevalence of M. canis infection decreased markedly in the 2000s. The prevalence of T. mentagrophytes has decreased in Korea since 2005 ( 20 ). Choe et al ( 33 ) reported that the prevalence of T. verrucosum infection decreased much more in the 2000s than in the late 1900s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lee et al ( 19 ) also reported that the prevalence of M. canis infection decreased markedly in the 2000s. The prevalence of T. mentagrophytes has decreased in Korea since 2005 ( 20 ). Choe et al ( 33 ) reported that the prevalence of T. verrucosum infection decreased much more in the 2000s than in the late 1900s.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, T. schenleinii has disappeared from Korea ( 8 ). Similarly, T. mentagrophytes and M. canis have been decreasing in prevalence since the 2000s ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent report from South Korea on a group of patients with Trichophyton mentagrophytes , which is the second most common type of tinea pedis, found that infection was more prevalent among males than females and was highest among those aged between 30-49 years [5]. They also reported that the number of infected patients decreased since 2005; however, the robustness of these results may be low since it was based on data from only a few hospitals that targeted 6,250 patients over 21 years.…”
Section: Discussionmentioning
confidence: 99%
“…No RS, entre os meses de novembro de 2010 e agosto de 2011, foram analisados laudos de pacientes submetidos a exames micológicos, com suspeita de micose superficial, cutânea e profunda, encaminhados a um laboratório no município de Novo Hamburgo, da Região do Vale dos Sinos. Dos resultados positivos para micoses superficiais e cutâneas, envolvendo pele e unha, a maioria (38,70%) foi devido a T. mentagrophytes, sendo que as demais espécies relacionadas com esse tipo de micose, em ordem de ocorrência, foram Candida spp., M. canis, T. rubrum e T. interdigitale 21 .…”
Section: Dermatofitoses Agentes Etiológicos -Fungos Dermatófitosunclassified